Predictors of atrial fibrillation in patients with COVID-19 - V. I. Podzolkov; A. I. Tarzimanova; A. E. Bragina; I. Zh. Loriya; A. E. Pokrovskaya; E. E. Bykova; A. A. Ivannikov; I. I. Shvedov; D. D. Vanina (Российский кардиологический журнал)
Early diagnosis of atrial fibrillation (AF) predictors in coronavirus disease 2019 (COVID-19) and the appointment of additional therapy to prevent arrhythmias will improve the prognosis of patients.Aim. To identify predictors of AF in patients with COVID-19.Material and methods. This retrospective study included 1473 patients hospitalized with COVID-19. Depending on AF occurrence, the patients were divided into 2 groups as follows: group I included 95 patients with AF episodes during hospitalization; group II consisted of 1378 patients who did not have AF during hospitalization. All patients underwent a complete blood count and urine tests, a biochemical and coagulation blood tests, 12-lead electrocardiography, chest computed tomography (CT), and echocardiography.Results. Chest CT found that lung tissue involvement in patients of group I was significantly greater than in group II (p<0,05). The number of patients with significant lung involvement >50% (CT-3 and CT-4) was significantly higher in the AF group than in the control group. The average room air oxygen saturation upon admission to the hospital were significantly lower in patients with AF than in the comparison group (p<0,05). Multivariate analysis showed that following factors have a significant effect on AF development in COVID-19 patients: age >60 years, hypertension, coronary artery disease, heart failure, increased left atrial volume, large lung tissue involvement, and increased interleukin- 6 level.Conclusion. There are two following groups of predictors initiating AF in COVID-19: generally known (older age, cardiovascular disease, increased left atrial volume) and those that determine the severe COVID-19 course (large lung damage and high interleukin-6 levels).